Using transcriptome Shannon entropy to evaluate the off-target effects and safety of insecticidal siRNAs - Wei-hua MA; Tong WU; Zan ZHANG; Hang LI; Gong-ming SITU; Chuan-lin YIN; Xin-hai YE; Meng-yao CHEN; Xian-xin ZHAO; Kang HE; Fei LI (Journal of Integrative Agriculture, 2022)
A recent breakthrough in agricultural biotechnology is the introduction of RNAi-mediated strategies in pest control. However, the off-target effects of RNAi pest control are still not fully understood. Here, we studied the off-target effects of two insecticidal siRNAs in both target and non-target insects. The results revealed that off-target effects of insecticidal siRNAs occur widely in both target and non-target insects. We classified the expression-changed genes according to their homology to the siRNA-targeted gene, related KEGG pathways with the siRNA-targeted gene and continuous matches with siRNAs. Surprisingly, the unintended significant changes in gene expression levels did not strictly match with the number of contiguous nucleotides in the siRNAs. As expected, the expression of small portions of the homologous and KEGG-related genes were significantly changed. We calculated the Shannon entropy of the transcriptome profile of the insects after injecting them with insecticidal siRNAs. Though hundreds of genes were affected in their expression levels post siRNA-treatment, the Shannon entropy of the transcriptome remained unchanged, suggesting that the transcriptome expression was balanced. Our results provide evidence that siRNAs cross-reacted with individual genes in non-target species, but did not have significant effects on the integrity of the transcriptome profiles in either target or non-target species on a genomic scale. The metric we proposed can be used to estimate the off-target effects of insecticidal siRNAs, which might be useful for evaluating the safety of RNAi in pest control.